FAKTOR-FAKTOR YANG MEMPENGARUHI PENAWARAN CABAI MERAH BESAR (Capsicum Annuum L) DI KABUPATEN ROKAN HULU - Ari Akbar; Defidelwina; Sischa Febriani Yamesa Away (SUNGKAI, 2025)
Large red chili is one type of vegetable with high economic value that is often used as a cooking spice in everyday life. This study aims to analyze the factors that influence supply and measure the elasticity of supply of large red chili in Rokan Hulu Regency. The method used is multiple linear regression. The data used is monthly secondary data from the Food Security Service and the Central Statistics Agency processed using the Eviews 7 application. The data was processed from 2021-2023. The results of the study show that the price of large red chili has a positive effect on supply with a coefficient of 0.0845, and is significant at alpha 10%. The price of cayenne pepper has a positive effect on supply with a coefficient of 0.0198, population and onion prices have a significant effect at alpha 5% with 0.000 each. The results of the elasticity analysis show that the price of large red chili is inelastic with an elasticity value of 0.2442, meaning that a 10% price increase only increases supply by 2.44%. The price of cayenne pepper is inelastic with an elasticity value of -0.4373, meaning that a 10% price increase only increases supply by 4.37%. The population is inelastic with an elasticity value of -24.4365, meaning that a 10% price increase only increases supply by 24.4% and the price of onions is inelastic with an elasticity value of -0.7741, meaning that a 10% price increase only increases supply by 7.7%.